Static and dynamic analyses of fracture fixation bone-plate systems for different plate materials and dimensions - Erdem, Serkan; Gur, Mustafa; Kaman, Mete Onur (Ios Press, 2018)
BACKGROUND: Various techniques have been developed in the treatment of fractures. One of these techniques is the internal fixation, which has an important place in practice. OBJECTIVE: In this study, fractured tibia bone has been treated with implants as numerically to investigate the stress behavior and the effect of plate material, shape and dimensions under pressure load. METHODS: The outer part of the bone is chosen as orthotropic and the inner part is chosen as isotropic material. The plate has been modeled to take the form of the bone surface and the finite element method has been used for numerical analysis. The effect of stress on bones and implants has been examined for 1% healing by changing the plate length, plate width and plate material. RESULTS: It has been observed that the increase in plate length decreases cortical bone stress until a specific length. On the other hand, the increase in plate width has increased the stress on the bone. CONCLUSIONS: It is important to form the appropriate plate surface to the bone surface in terms of compliance with the bones.
Keywords: Internal fixation; implant; finite element analysis; crack; tibia